Frontier life : copyright-free illustrations for lovers of history - Kalman, Bobbie (New York, N.Y. : Crabtree Pub., 1998)
Etchings and accompanying text depict various aspects of frontier life, including homes, hunting, and frontier towns.
8 - 10 years
Keywords: Frontier and pioneer life -- Pictorial works -- Juvenile literature. -- United States; Frontier and pioneer life -- Pictorial works -- Juvenile literature. -- West (U.S.); Frontier and pioneer life; United States -- Social life and customs -- Pictorial works -- Juvenile literature; West (U.S.) -- Social life and customs -- Pictorial works -- Juvenile literature; United States -- Social life and customs